Modeling of 1D Au plasmonic grating as efficient gas sensor. (15th November 2019) - Afsheen, Sumera; Iqbal, Tahir; Aftab, Muhammad; Bashir, Almas; Tehseen, Aqsa; Khan, Muhammad Yaqoob; Ijaz, Mohsin
Abstract: Gas-sensor reported here consist of a sensing chip of a metallic grating designed on gold (Au) film over a glass substrate which has been modelled using finite element analysis (FEA). The Au is layered in the form of horizontal nano-strips with a periodic nano-sized gap known as slit-width. The transverse magnetic (TM) light illuminates the metallic films from substrate side at normal incidence. The transmission loss spectrums have been extracted for 0th order diffraction for different physical interpretations. The several combinations of periodicity and slit width have been optimized by taking slit width as half of periodicity. The refractive index sensitivity achieved at optimal geometrical parameters is noteworthy and it is reported to be 599 (nm/RIU) at a spatial period of 660 nm. The novel theoretical results has been supported by far field and near field analysis. The design suggested in this report is important becuase of the wavelength range that lie in the visible region where most of the real life spectrometers works. Such sensors can be applicable in industries for detection of toxic gases and harmful metallic pieces in atmosphere.